ANALISIS IMPLEMENTASI MANAJEMEN CASEMIX DALAM PENINGKATAN PENDAPATAN DI RSUD X - Herdiani, Erni; Aziz, Abdul; Subardi, Arda Yunita; Dwinuarisha, Eggie (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2024)
Hospitals are currently facing high VUCA (vulnerability, uncertainty, complexity & ambiguity) challenges. In order to remain able to compete in a healthy manner, to grow and develop successfully in accordance with its vision and mission, hospitals need to respond to these changes quickly and appropriately. One form of response to these changes is that hospital management understands the Casmix system and can implement it. Therefore, research was carried out at Hospital The research was carried out using a qualitative method with a descriptive analytical approach where this research carried out observations of the management casemix activity process, documented and interviewed and analyzed the research results. The results obtained are the implementation of casemix management at RSUD X in the Casemix unit. It can be concluded that Casemix management is less than optimal. The obstacles to less than optimal casemix management are the lack of optimal mapping of workload analysis and empowerment of casemix team personnel evenly and optimally and the lack of re-socialization of both coding and clinical pathway compliance for medical service teams. Apart from that, the work mechanism does not yet contain minimum time standards for each step of filing, coding and submission and there is no completeness checklist so that monitoring and eval__uation cannot be carried out optimally. Apart from that, RME is not yet optimal, especially in inpatient settings, it is not yet integrated and does not include interoperability. Optimization can be carried out, including by optimizing the casemix team by analyzing workloads and job descriptions whose performance indicators can be measured by updating existing SKs according to the analysis carried out, optimizing BPJS Claims SOPs, equipped with time limits for each step, making it easier to carry out monitoring and eval__uation. It is also necessary to prepare a checklist for completeness of files so that proper monitoring and eval__uation can be carried out, improving supporting facilities, namely RME, is very vital to be able to carry out Competency improvement can continue to be carried out periodically, especially in inpatient settings, periodically increasing competency for casemix teams and resocializing clinical pathways.